The Role of Digital Villages in Tourism-Based Community Economic Empowerment Efforts in Sidomulyo Village, Silo District, Jember Regency - Sugianto, Sugianto (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2023)
This study aims to explain the role of digital villages in efforts to empower the community's economy in Sidomulyo Village, Silo District, Jember Regency, as well as explain BUMDes' efforts for tourism-based community economic empowerment in Sidomulyo Village, Silo District, Jember Regency. The method used is a qualitative approach to the type of descriptive research. In determining the informants researchers used a purposive technique . While data collection techniques using observation, interviews, and documentation. The results of this study are the role of digital villages in efforts to empower the economy through a process including creating a village information system (SID) by creating the MallDesa application. BUMDes' efforts to empower tourism-based community economies in Sidomulyo village, Silo sub-district, Jember district in realizing an empowerment in the Raja Raja Domba tourism are using several stages including capital assistance, infrastructure assistance, mentoring assistance, and marketing assistance.